Project ImPACT: Hypertension Outcomes of a Pharmacist-Provided Hypertension Service - Carrie Wentz Nemerovski; Maria Young; Nicholas Mariani; Carol Bugdalski-Stutrud; Lynette R. Moser (University of Minnesota Libraries Publishing, 2013)
Objective: To evaluate the impact of pharmacists, working collaboratively with patients, on blood pressure control, lifestyle goal setting, adherence to antihypertensive therapy, patient knowledge and satisfaction, and modification of cardiovascular risk factors. Methods: Self-declared hypertensive patients met with the pharmacist for blood pressure monitoring, lifestyle goal setting, and education about medications and disease state on four occasions over a 6-month period. Practice innovation: A community pharmacy partnered with an employer wellness plan to provide education and monitoring for patients with hypertension based on home blood pressure readings obtained using monitors that wirelessly transmit information to the pharmacist. Main outcome measure(s): Percentage of patients at blood pressure goal, mean blood pressure, percentage of patients with lifestyle goals, medication adherence, patient knowledge and satisfaction, and modification of cardiovascular risk factors. Results: Patients not at their goal blood pressure at baseline had a significant decrease in blood pressure and a significant increase in achievement of their blood pressure goals. Across the population, no significant changes were seen in the primary outcome, lifestyle goals, medication adherence or modification of cardiovascular risk factors. Patient knowledge increased from baseline and satisfaction with the service was high. Conclusion: Blood pressure control improved in patients not at their treatment goal. All patients increased their knowledge about hypertension and reported high satisfaction with the pharmacy service. Pharmacy services should be offered to patients who are more likely to reap a benefit. Home blood pressure readings are useful to inform clinical decision making and supplement patient consultation within the pharmacy setting.   Type: Original Research